Neck muscle vibration induces lasting recovery in spatial neglect. Issue 4 (1st October 2002) - Schindler, I; Kerkhoff, G; Karnath, H-O; Keller, I; Goldenberg, G
Abstract : Objectives: To evaluate whether neck muscle vibration is an effective technique for neglect rehabilitation, with lasting beneficial effects. Methods: The effects of differential treatment of visual exploration training alone or in combination with neck muscle vibration were evaluated in a crossover study of two matched groups of 10 patients suffering from left sided neglect. Each group received a sequence of 15 consecutive sessions of exploration training and combined treatment. The effects of treatment were assessed with respect to different aspects of the neglect disorder such as impaired perception of the egocentric midline, exploration deficits in visual and tactile modes, and visual size distortion. The transfer of treatment effects to activities of daily living was examined by a reading test and a questionnaire of neglect related everyday problems. All variables were measured six times: three baseline measurements, two post-treatment measurements, and one follow up after two months. Results: The results showed superior effects of combination treatment. A specific and lasting reduction in the symptoms of neglect was achieved in the visual mode, which transferred to the tactile mode with a concomitant improvement in activities of daily living. The improvement was evident two months after the completion of treatment. In contrast, isolated exploration training resulted in only minor therapeutic benefits in visual exploration without any significant transfer effects to other tasks. Conclusions: Neck muscle vibration is a decisive factor in the rehabilitation of spatial neglect and induces lasting recovery when given as a supplement to conventional exploration training.